2021
DOI: 10.1155/2021/8833502
|View full text |Cite
|
Sign up to set email alerts
|

Support Measures to Prevent the Deformation and Failure of a Carbonaceous Mudstone Tunnel

Abstract: A carbonaceous mudstone tunnel is a type of soft rock tunnel. There is little research on the prevention and control measures for the deformation and failure of carbonaceous mudstone tunnels. In this article, we investigated the construction of the Qiguding carbonaceous mudstone tunnel in Meizhou City, Guangdong Province, China. We monitored and analyzed the deformation and stress characteristics of a section under the original support scheme. The monitoring data showed that this section had large peripheral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Mudstone is a type of soft rock that exhibits distinctive engineering properties. It has unique characteristics, including rheology, swelling, disintegration, and softening [12][13][14][15]. The strength of mudstone is typically weak, rendering the surrounding rock highly susceptible to significant displacement during tunnel excavation, which has a significant impact on construction safety.…”
Section: Engineering Backgroundmentioning
confidence: 99%
“…Mudstone is a type of soft rock that exhibits distinctive engineering properties. It has unique characteristics, including rheology, swelling, disintegration, and softening [12][13][14][15]. The strength of mudstone is typically weak, rendering the surrounding rock highly susceptible to significant displacement during tunnel excavation, which has a significant impact on construction safety.…”
Section: Engineering Backgroundmentioning
confidence: 99%
“…A large number of studies have shown that bolts can improve the mechanical parameters of surrounding rock, e ectively strengthen the bearing capacity of surrounding rock, and reduce the deformation of surrounding rock [43][44][45][46].…”
Section: Design Of Combined Support Scheme As Shown Inmentioning
confidence: 99%